Anticholinergic delirium superimposed on severe cognitive deficit secondary to benzhexol and flupenthixol decanoate: A dilemma in management - Misron, Siti Nor Fadhlina; Othman, Zahiruddin; Misron, Lukmanul Hakim (Yuzuncu Yil University, 2018)
The first and second generation antipsychotics are associated with cognitive impairment through the antidopaminergic and anticholinergic effects. However serious anticholinergic adverse events may occur in susceptible individual, such as being illustrated in this case, even though flupenthixol decanoate has never been reported to cause them. The concomitant use of anticholinergic medication to counter the antidopaminergic side effects may further accentuate this condition and leads to delirium despite within the therapeutic dosage